A Cross-Sectional Survey on Medication Management Practices for Noncommunicable Diseases in Europe During the Second Wave of the COVID-19 Pandemic - Ágh, Tamás; van Boven, Job FM; Wettermark, Björn; Menditto, Enrica; Pinnock, Hilary; Tsiligianni, Ioanna; Petrova, Guenka; Potočnjak, Ines; Kamberi, Fatjona; Kardas, Przemyslaw; , European Network to Advance Best practices & technoLogy on medication adherencE (ENABLE) (Frontiers in Pharmacology, 2021)
Maintaining healthcare for noncommunicable diseases (NCDs) is particularly important during the COVID-19 pandemic; however, diversion of resources to acute care, and physical distancing restrictions markedly affected management of NCDs. We aimed to assess the medication management practices in place for NCDs during the second wave of the COVID-19 pandemic across European countries. In December 2020, the European Network to Advance Best practices & technoLogy on medication adherencE (ENABLE) conducted a cross-sectional, web-based survey in 38 European and one non-European countries. Besides descriptive statistics of responses, nonparametric tests and generalized linear models were used to evaluate the impact on available NCD services of the number of COVID-19 cases and deaths per 100,000 inhabitants, and gross domestic product (GDP) per capita. Fifty-three collaborators from 39 countries completed the survey. In 35 (90%) countries face-to-face primary-care, and out-patient consultations were reduced during the COVID-19 pandemic. The mean±SD number of available forms of teleconsultation services in the public healthcare system was 3±1.3. Electronic prescriptions were available in 36 (92%) countries. Online ordering and home delivery of prescription medication (avoiding pharmacy visits) were available in 18 (46%) and 26 (67%) countries, respectively. In 20 (51%) countries our respondents were unaware of any national guidelines regarding maintaining medication availability for NCDs, nor advice for patients on how to ensure access to medication and adherence during the pandemic. Our results point to an urgent need for a paradigm shift in NCD-related healthcare services to assure the maintenance of chronic pharmacological treatments during COVID-19 outbreaks, as well as possible future disasters.